Satisfacción de la atención de enfermería en usuarios del Centro de Salud Motupe de la Ciudad de Loja - Gordillo Ramón, María Isabel (2023)
Nursing care satisfaction is an important aspect in health care; To achieve this, services must be offered in a timely, optimal and quality manner according to the required needs of the user. For this reason, it is important to carry out constant evaluations of the care provided, to identify the aspects in which there is a deficit in the Nursing act in order to correct and improve. The objective of this study was to analyze the satisfaction of nursing care in users of the Motupe Health Center of the City of Loja. It is a study with a quantitative approach, with a descriptive and cross-sectional scope, whose sample consisted of 67 users. For data collection, the CAREQ instrument was applied, created by its author Patricia Larsson, it consists of 46 items where nursing care is evaluated, associated with the dimensions of accessibility, explains and facilitates, comfort, anticipates, maintains relationship of trust, monitors and follows up. The results obtained related to user satisfaction with nursing care were medium at 95.7%, the best qualified scale was Accessibility with 11.6%, while the lowest qualified dimension was Explains and facilitates with 4.3%. Despite the results obtained, there are aspects to improve such as: providing information, in which full attention must be paid in order to achieve better results, and therefore users and family members feel satisfied with the care provided by the staff of nursing